Public View as an Aggravating Factor in Joint Violence According to Article 170 Paragraph (2) of the Criminal Code: Vis Publica Sebagai Pertimbangan Pemberat Pidana dalam Kekerasan Bersama Menurut Pasal 170 Ayat (2) KUHP - Purba, Gilbert; Rahaditya, Rahaditya (Universitas Muhammadiyah Sidoarjo, 2026)
General Background: Violence committed collectively poses broader social risks because it disrupts public order and triggers wider societal anxiety. Specific Background: In Indonesian criminal law, vis publica in Pasal 170 KUHP functions as a key qualifier distinguishing ordinary assault from public-order crimes, yet its judicial interpretation remains inconsistent. Knowledge Gap: Existing scholarship has not clarified how vis publica should operate as a basis for sentencing aggravation under Pasal 170 ayat (2) KUHP, nor how judges should evaluate its causal relevance to social disturbance. Aims: This study analyzes the juridical status of vis publica as a judicial consideration in imposing aggravated penalties for collective violence. Results: Findings show that vis publica acts as a legal threshold for classifying the offense as a public-order crime, but it only justifies aggravated sentencing when judges demonstrate its concrete contribution to expanding social harm. Novelty: This research formulates a structured reasoning model requiring judges to link public visibility with measurable disturbance before escalating punishment. Implications: Strengthening doctrinal clarity on vis publica supports proportional sentencing, enhances legal certainty, and improves consistency in judicial decision-making in collective-violence cases. Highlights: Vis publica is the legal threshold that transforms individual assault into a public-order crime. Aggravated sentencing requires a proven causal link between public visibility and expanded social harm. Judicial reasoning must be structured, proportional, and grounded in measurable disturbance. Keywords: Vis Publica, Pasal 170 KUHP, Collective Violence, Sentencing Aggravation, Public Order.